Hyperacute Subarachnoid Hemorrhage on T2-Weighted MR Images - Rumboldt, Zoran; Kalousek, Miljenko; Castillo, Mauricio (American Journal of Neuroradiology, 2003)
Summary: We describe a case of hyperacute subarachnoid and intraventricular hemorrhage from a ruptured aneurysm, which occurred while the patient was undergoing MR imaging. Compared with CSF, the blood in the subarachnoid space had slightly lower signal intensity on T2*-weighted gradient-echo images and increased signal intensity on T2-weighted spin-echo images. This finding differs from the generally accepted MR appearance of intracranial hemorrhage and should be recognized to ensure proper patient care.